Metal triflates and triflimides as Lewis "superacids": preparation, synthetic application and affinity tests by mass spectrometry†. (7th September 2012) - Gal, Jean‐François; Iacobucci, Claudio; Monfardini, Ilaria; Massi, Lionel; Duñach, Elisabet; Olivero, Sandra
<x xml:space="preserve">Abstract</x> Metal salts of triflic acid, CF3SO2OH and of triflimidic acid, [CF3SO2]2NH, often called "Lewis superacids", are powerful catalysts for several classes of reactions. Typical applications developed at the Institut de Chimie de Nice during the last decade, mostly in the domain of inter‐ and intramolecular carbon–carbon, carbon–oxygen and carbon–sulfur bond formation, are illustrated. During the last three years, the characterization of metal triflates and triflimides by electrospray mass spectrometry was also accomplished in our Institute. Displacement of one anion of the salt by strong neutral ligands was developed as a mean for generating characteristic positive ions. In an effort toward the quantitative description of the ligand/metal bonding and the catalytic role of the Lewis acid, a ligand competition method was devised. An exploratory study attests that subtle structural effects on the donor/acceptor interaction can be evidenced using this simple mass spectrometric method. Copyright © 2012 John Wiley & Sons, Ltd.